The foreign policy of the European Union assessing Europe's role in the world - Bindi, Federiga M.; Angelescu, Irina (Brookings Institution Press, 2012)
"Explores European foreign policy and the degree of European Union success in proposing itself as a valid international actor, drawing from the expertise of scholars and practitioners in many disciplines. Addresses issues past and present, theoretical and practice-oriented, and country- and region-specific"--Provided by publisher.